Effect of Milking Time Intervals on Production and Quality of Friesian Holstein - Tedi Akhdiat; Hilman Permana; Nilawat Widjaja; Raden Febrianto Christi; Dini Elsa Alfiani (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
Milking is the act of removing milk from the udder on purpose to get maximum milk production. A reasonable milking interval will affect the amount of milk production. This research aims to know the extent of the milking time interval affecting Friesian Holstein dairy cow milk production and the interval of milking time that produces the best production and quality of Friesian Holstein. The research method was an experiment using a completely rand randomized with four treatments, namely: treatments 1 was 16:8 hours time delivery interval (TDI) dairy cow; treatments 2: time delivery interval (TDI) 15:9 hours; treatment 3: delivery time interval (TDI) 14:10 hours; treatment 4: time delivery interval (TDI) 13:11 hours. The observed variables are milk production and milk quality. The data were analyzed using verbal if any effect of treatment was done Duncan's distance test. Based on the results and discussion, the milking time interval significantly impacts milk production and water content. Still, it has no significant effect on the density, protein content, and milk fat content, 13:11 hours milking interval time produces the most milk and water content.